PEMAHAMAN MAHASISWA AKUNTANSI TERHADAP KONSEP DASAR AKUNTANSI BERDASARKAN ASAL SEKOLAH DAN TINGKAT SEMESTER - Djoko Kristianto, Intantri Purwanti, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this research is to analyze the difference of understanding of the basic concepts in accounting student who comes from a different school Department, high school majoring in natural science and social science, and SMK majoring in accounting and on the level of the semester, there are interactions influence the origin school and extent of semesters toward basic concepts of accounting. This research using the method of survey which is done directly on the student accounting economic faculty of University of Slamet Riyadi. The analysis of the data using Analysis of Variance (ANOVA) to measure the difference comprehension the basic concepts of accounting between the origin school and the level of semesters. The results showed that the difference comprehension the basic concepts of accounting based on the origin of the school obtained p value 0.003 >0.05, difference comprehension basic concepts of accounting based on the semester obtained p value 0,000 > 0,05 so it can be said there are differences in the average Understanding Accounting Concepts by origin school and semester. Influence of interaction of the basic comprehension of Accounting Difference obtained p value 0,041> 0,05 so can be said to be there are interactions influence the origin school and semester.Keywords: origin school, level of semester, basic accounting concept